Tuning of ferrimagnetic nature and hyperfine interaction of Ni2+ doped cobalt ferrite nanoparticles for power transformer applications. Issue 8 (1st June 2018) - Srinivasamurthy, K.M.; Angadi V, Jagadeesha; Kubrin, S.P.; Matteppanavar, Shiddaling; Sarychev, D.A.; Kumar, P. Mohan; Azale, Haileeyesus Workineh; Rudraswamy, B.
Abstract: Ferrites may contain single domain particles which gets converted into super-paramagnetic state near critical size. To explore the existence of these characteristic feature of ferrites, we have performed magnetization(M-H loop) and Mössbauer spectroscopic studies of Ni 2+ substitution effect in Co1-x Nix Fe2 O4 (where x = 0, 0.25, 0.5, 0.75 and 1) nanoparticles were fabricated by solution combustion route using mixture of carbamide and glucose as fuels for the first time. As prepared samples exhibit spinel cubic structure with lattice parameters which decreases linearly with increase in Ni 2+ concentration. The M-H loops reveals that saturation magnetization(Ms ), coercive field(Hc ) remanence magnetization(Mr ) and magnetron number(ηB ) decreases significantly with increasing Ni 2+ substitution. The variation of saturation magnetization has been explained on the basis of Neel's molecular field theory. The coercive field(Hc ) is found strongly dependent on the concentration of Ni 2+ and decrease of coercivity suggests that the particles have single domain and exhibits superparamagnetic behavior. The Mössbauer spectroscopy shows two ferrimagnetically relaxed Zeeman sextets distribution at room temperature. The dependence of Mössbauer parameters such as isomer shift, quadru pole splitting, line width and hyperfine magnetic field on Ni 2+ concentration have been discussed. Hence our results suggest that synthesized materials are potential candidate for power transformer application.